Comparison between endovascular and surgical treatment of acute arterial occlusive mesenteric ischemia - Kase, Karri; Blaser, Annika Reintam; Koitmäe, Merli; Talving, Peep; Tamme, Kadri; Acosta, Stefan; Björck, Martin; Bala, Miklosh; Bodnar, Zsolt; Cahenzli, Martin; Casian, Dumitru; Demetrashvili, Zaza; et al. (BioMed Central, 2025)
Background The optimal strategy for initial treatment of acute occlusion of superior mesenteric artery (SMA) is debated. The aim of the study was to compare the effectiveness, timelines and outcomes of endovascular versus open surgical treatment in patients with acute SMA occlusion. This was a preplanned substudy of the prospective observational multicenter AMESI (Acute MESenteric Ischaemia) study. Methods Patients with SMA occlusion were divided into surgical and endovascular treatment groups. The surgical group included patients initially subjected to open surgical treatment with surgical or hybrid revascularization or intestinal resection only. The endovascular group included patients initially revascularized endovascularly and was further divided according to treatment effectiveness. Patients were also categorized according to revascularization or no revascularization, and subanalysis performed for different revascularization methods. Baseline and outcome comparisons were made using Fisher and Mann–Whitney U tests. Risk-factors for in-hospital mortality were analysed using a logistic regression model. Results Of 158 patients 107 had surgical and 51 endovascular treatment. The surgical group had higher baseline illness severity scores, higher C-reactive protein and lactate values. The mortality in the endovascular effective, endovascular insufficient as monotherapy and surgical groups was 2.9%, 41.2% and 45.8%, respectively. In multivariable analysis surgery was not an independent risk factor for in-hospital mortality. The rate of arterial embolism was higher in the endovascular revascularization as monotherapy insufficient treatment group (10/17) compared to the endovascular revascularization as monotherapy effective (5/34) and surgical (27/107) groups. We could not identify useful best thresholds for discriminating between effective and insufficient endovascular treatment. Analysis comparing the effect of any revascularization versus no revascularization on in-hospital mortality did not show a clear benefit of revascularization and the method of revascularization did not independently influence mortality. Conclusion The beneficial effect of endovascular compared to surgical treatment in unadjusted analyses is largely explained by selection of patients. None of the compared management approaches had an independent effect on mortality. The choice between endovascular and surgical treatment should not be based solely on the time elapsed from symptom onset but rather on the patient’s general condition and possibly on the cause of SMA occlusion.